Roberto Calasso - René Girard Lecture, November 5th, 2014 - Calasso, Roberto (http://www.imitatio.org, 2014)
Roberto Calasso, publisher of Adelphi Edizioni and author of works including The Ruin of Kasch, La Folie Baudelaire, and Ardor gives a lecture at Stanford in honor of René Girard, entitled "The Last Superstition." Recorded November 5, 2014